Down the Hole - Slater, Scott; Ming, Adam (New York : Clarion Books, an imprint of HarperCollinsPublishers, 2023)
"When a suspiciously polite fox attempts to coax his next meal out of a burrow, he is met with a clever rabbit who has been cooking up a surprise for this very moment"--
Keywords: Rabbits -- Juvenile fiction; Foxes -- Juvenile fiction; Rabbits -- Fiction; Foxes -- Fiction; Picture books